(untitled) (American Journal of Economics and Business Innovation, 2025)
The business structure of Iraqi Small and Medium Enterprises faces transformations due to Digital Transformation. The main economic driver of Iraq consists of SMEs that encounter multiple barriers to technological implementation mainly due to poor infrastructure along with financial backing and specialized expertise deficiencies across local spaces. The maximum business benefits await Small medium Enterprises (SMEs) when they accept digital transformation. The research investigates digital technology utilization by Iraqi SME businesses and their work model evolution. The study uses both quantitative and qualitative approaches to determine its research methodology. The study confirmed that adopting digital transformation would lead both to operational improvements and enhanced performance and business competitive advantage while recognizing existing implementation challenges.